2011
DOI: 10.1007/s10856-011-4408-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyaluronic acid on bacterial and fungal species, including clinically relevant opportunistic pathogens

Abstract: Hyaluronic acid (HA) has several clinical applications (aesthetic surgery, dermatology, orthopaedics and ophtalmology). Following recent evidence, suggesting antimicrobial and antiviral properties for HA, we investigated its effects on 15 ATCC strains, representative of clinically relevant bacterial and fungal species. The in vitro system employed allowed to assess optical density of broth cultures as a measure of microbial load in a time-dependent manner. The results showed that different microbial species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 16 publications
2
65
0
1
Order By: Relevance
“…It is a main component of extracellular tissues abundant in skin, connective tissue, synovial fluid, and vitreous humor. 13 HA polymers organize into a reticular structure and produce a molecular framework. 20 This characteristic enables HA to be used as an ingredient in several artificial tears.…”
Section: Yadav Chuck and Parkmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a main component of extracellular tissues abundant in skin, connective tissue, synovial fluid, and vitreous humor. 13 HA polymers organize into a reticular structure and produce a molecular framework. 20 This characteristic enables HA to be used as an ingredient in several artificial tears.…”
Section: Yadav Chuck and Parkmentioning
confidence: 99%
“…22 Dose-dependent antibacterial effects of HA were reported in some gram-positive (Staphylococcus epidermidis) and gram-negative (Escherichia coli) bacteria, and the addition of HA in the culture medium can invoke relatively inhibitory effects on growth of planktonic P. aeruginosa, although the exact mechanism remains unclear. 13,23 Further research regarding the antimicrobial effects of HA is necessary, but is beyond the scope of this article.…”
Section: Yadav Chuck and Parkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ardizzoni et al 41 reported such effects for HA. In particular staphylococci, enterococci, Streptococcus mutans, two Escherichia coli strains, Pseudomonas aeruginosa, Candida glabrata and C. parapsilosis displayed for HA dose dependent growth inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…15 In terms of bacterial and fungal species, staphylococci, enterococci, Streptococcus mutans, two Escherichia coli strains, Pseudomonas aeruginosa, Candida glabrata, and Candida parapsilosis exhibit hyaluronic acid dose-dependent growth inhibition, while E. coli ATCC 13768 and Candida albicans do not exhibit any effect, and Streptococcus sanguinis is favored by high hyaluronic acid dose. 16 In summary, hyaluronic acid produces changes in the immune system, inflammatory mediators, and markers of oxidative stress, and may interact with pathogens. This evidence should be taken into account when performing hyaluronic acid-based delivery of drugs and medical procedures in clinical practice.…”
Section: Hyaluronic Acid and Nanomedicinementioning
confidence: 99%